Optimization Of The Utilization Of Productive Zakat For The Economic Empowerment Of Mustahik In The MSME Culinary Sector (A Case Study Of Lazismu Yogyakarta Region) - Miftahul Janah; Nugraheni Rintisari (SEAN Institute, 2024)
This study aims to examine the procedures implemented by Lazismu Yogyakarta Region in their MSME Empowerment program through the productive utilization of zakat. The goal is to assess whether these procedures are optimal and have successfully achieved the program's objectives of enhancing the welfare of the poor through sustainable economic means. A descriptive qualitative research method was employed for this study, which was conducted at Lazismu Yogyakarta Region. The informants included the manager and the head of the productive zakat fund distribution section at Lazismu Yogyakarta Region, along with three mustahik from the culinary sector who received productive zakat assistance. Data analysis was performed using Pattern Matching with Atlas.ti tools. The findings indicate that the productive zakat utilization for economic empowerment of mustahik in the culinary MSME sector in Lazismu Yogyakarta Region can be optimized by further enhancing training, mentoring, and the selection process for recipients of productive zakat assistance.